Antaseden Kinerja Pegawai PT. Angkasa Pura II Bandara Silangit - Siti Normi Sinurat; Kristanty M N Nadapdap; Thomas Sumarsan Goh; Saur Melianna; Markus Doddy Simanjuntak (Manajemen: Jurnal Ekonomi USI, 2024)
Human Resources (HR) are an important asset for every organization, including PT. Angkasa Pura II Silangit Airport, North Sumatra Province. Effective HR management through good leadership and proper training is essential to achieve organizational goals. This study aims to analyze the effect of leadership style and job training on employee performance at PT. Angkasa Pura II Silangit Airport, North Sumatra Province. Data were obtained through a questionnaire filled out by 64 respondents in July 2024, with a response rate of 100%. The results showed that timely job training and participatory leadership styles had a positive and significant impact on employee performance. Ticket sales data showed fluctuations from year to year, which was consistent with the lack of training and leadership style. A study of respondents showed that employee performance can be improved through the opportunity provided by leadership to convey input and complaints. Training that is relevant to operational needs and technological developments has been shown to improve employee competence and productivity. The conclusion of this study is that structured job training and good leadership style significantly improve employee performance at PT. Angkasa Pura II Silangit Airport, North Sumatra Province. Recommendations from this study include the importance of effective communication between management and employees and the development of ongoing training programs to maintain employee competence and motivation. It is hoped that the implementation of these strategies will optimize the overall performance of the organization